Epidemiological trends and risk factors in major burns patients in South Korea: A 10-year experience. Issue 1 (February 2015) - Seo, Dong Kook; Kym, Dohern; Yim, Haejun; Yang, Hyeong Tae; Cho, Yong Suk; Kim, Jong Hyun; Hur, Jun; Chun, Wook
Highlights During 2003–2012, 4481 major burns patients were treated in our burns center. Mortality rate decreased during the study period, but nevertheless remained high. Flames and scalds caused most burns in those aged ≥21 and ≤20 years, respectively. Age, sex, burn size and full-thickness and inhalation injuries predicted mortality. ABSI was useful to predict mortality but overestimated mortality in older patients.